1991
DOI: 10.1111/j.1526-4610.1991.hed3109593.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Reactivity During Migraine Attacks: A Transcranial Doppler Study

Abstract: We measured vascular reactivity--expressed i) as decrease in blood flow velocity (cm/sec) per vol% CO2 decrease due to voluntary hyperventilation and ii) as increase of blood flow velocity during the first minute after resuming normal ventilation, per vol% CO2 increase--in the middle cerebral and basilar artery of 48 migraineurs with attacks without aura, and 17 normal controls. We found no differences for both determinants of vascular reactivity between migraineurs during and outside an attack, and between mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…It is known that ischemic cerebral infarction preferentially affects the posterior cerebral artery distribution in migraine patients (5). Zwetsloot et al (17) did not find any difference in vasomotor reactivity in MCA and the basilar artery in MwoA compared to healthy subjects. Hyperreactivity, hyporeactivity, and no difference in reactivity were observed.…”
Section: Discussionmentioning
confidence: 83%
“…It is known that ischemic cerebral infarction preferentially affects the posterior cerebral artery distribution in migraine patients (5). Zwetsloot et al (17) did not find any difference in vasomotor reactivity in MCA and the basilar artery in MwoA compared to healthy subjects. Hyperreactivity, hyporeactivity, and no difference in reactivity were observed.…”
Section: Discussionmentioning
confidence: 83%
“…Compared to headache-free persons, interictal migraineurs showed increased cerebral vasoreactivity to CO 2 stimuli in some studies (17)(18)(19)(20)(21), but not in others (8,22,23). In response to cardiovascular autonomic tests such as head-up tilt, cold pressure or Valsalva manoeuver, the results were again conflicting (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In two relatively large studies with 31 [20] and 51 [21] patients, respectively, no decrease in blood flow velocity was found with TCD during migraine attacks. Furthermore, a recent magnetic resonance angiography (MRA) study found no MCA or extracranial part of the middle meningeal artery (MMA) dilatation during nitroglycerin-induced migraine ( n  = 20) [22].…”
Section: Results and Commentsmentioning
confidence: 99%